Conformation-specific display of 4E10 and 2F5 epitopes on self-assembling protein nanoparticles as a potential HIV vaccine - Wahome, Newton; Ambiel, Ina; Keppler, Oliver Till (Chemical biology and drug design, 2012)
The self-assembling protein nanoparticle (SAPN) is an antigen-presenting system that has been shown to be suitable for use as a vaccine platform. The SAPN scaffold is based on the principles of icosahedral symmetry, beginning from a monomeric chain that self-assembles into an ordered oligomeric state. The monomeric chain contains two covalently linked α-helical coiled-coil domains, an N-terminal de novo-designed pentameric tryptophan zipper and a C-terminal de novo-designed trimeric leucine zipper, which assemble along the internal symmetry axes of an icosahedron. In this study, we incorporated the membrane proximal external region (MPER) of HIV-1 gp41 from HXB2 into the N-terminal pentamer, referred to as MPER-SAPN, attempting to reproduce the α-helical state of the 4E10 epitope while maintaining a structurally less-constrained 2F5 epitope. Sprague-Dawley rats were immunized with MPER-SAPNs, and their sera were analyzed for induced humoral anti-HIV-1 responses. We show that high membrane proximal external region-specific titers can be raised via the repetitive antigen display of MPER on the SAPN without the need for adjuvant. However, none of the sera displayed a detectable neutralizing activity against HIV-1. Thus, 4E10- and 2F5-like neutralizing antibodies could not be elicited by MPER conformationally restrained in the SAPN context.
First published: 31 May 2012
Gesehen am 27.06.2018